Serum ammonia as an early predictor of in-hospital mortality in patients with glufosinate poisoning. (September 2019) - Lee, J; Lee, Y; Kim, YS; Choi, JG; Go, TH; Kim, H; Cha, YS
Background: The mortality rate associated with human glufosinate poisoning is high. We evaluated the usefulness of serum ammonia and sequential organ failure assessment (SOFA) and acute physiology and chronic health evaluation II (APACHE II) scores for early prediction of in-hospital mortality in glufosinate ammonium poisoning. Methods: A prospectively collected pesticide poisoning registry at a single academic medical center was retrospectively analyzed. Data were collected from consecutive patients diagnosed with glufosinate ammonium poisoning between May 2007 and February 2018. The initial serum ammonia level was defined as the highest serum ammonia level measured within 12 h after emergency department (ED) arrival. The SOFA and APACHE II scores were calculated using data obtained within the first 12 h after ED arrival. The patients were divided into survivor and nonsurvivor groups by in-hospital death status. Results: In total, 110 patients were included. Ten patients (9.1%) died in the hospital despite treatment. Median initial serum ammonia level was significantly higher in the nonsurvivor group than in the survivor group (219 (range: 158–792) versus 100.5 (range: 25–317) µg/dL, p < 0.001). Median SOFA and APACHE II scores in the survivor and nonsurvivor groups were 2 (range: 0–10) versus 5 (range: 1–8) ( p = 0.044) and 7 (range: 0–28) versus 16 (range: 8–22) ( p = 0.001), respectively. In the multiple logistic regression analysis, the initial serum ammonia level was the only independent predictor (cutoff value: 151 µg/dL). Conclusion: An initial serum ammonia level >151 µg/dL was an independent early predictor of in-hospital mortality in glufosinate ammonium poisoning.